Efficacy, safety, and controversy of ultrasound-guided radiofrequency ablation in the treatment of T1N0M0 papillary thyroid carcinoma - Yi, Zhang; Siyu, Li; Lijun, Fu; Danhua, Zhang; Jianhua, Li; Xinguang, Qiu (Frontiers in Oncology, 2022)
Objective: To evaluate the safety effect, and controversy on the treatment outcomes of radiofrequency ablation (RFA) for T1N0M0 papillary thyroid carcinoma (PTC). Materials and Methods: This study is assessed the medical records of 142 patients with primary T1N0M0 PTC tumors after RFA between 2014 and 2022. 4 patients underwent delayed surgery (DS) after RFA and 411 T1N0M0 patients underwent DS were recorded. Outcomes were compared between RFA and DS groups after propensity score matching (PSM). Results: The maximal diameter (MD) and volume (V) increased in months 1 (P < 0.01) and reduced after the 6-month follow-up (all P < 0.01). The disappearance and disease progression rates were 53.5 % and 2.1 %, respectively. The complication and disease progression rates had no significant difference between RFA and DS (P>0.05). In some cases, the tumors were not fully inactivated after RFA, and the central compartment lymph node (CCLN) were metastasis. The CCLN metastasis rate was 13.4%. MD, V and clustered calcifications were independent risk factors for CCLN metastasis by univariate analysis. Conclusions: RFA is an effective and safe treatment option in selected patients with solitary T1N0M0 PTC. There are the risks of tumor incompletely ablated and CCLN metastasis.